Genome-Wide Association Study for Spot Blotch Resistance in Hard Winter Wheat - Ayana, Girma T.; Ali, Shaukat; Sidhu, Jagdeep S.; Gonzalez Hernandez, Jose L.; Turnipseed, Brent; Sehgal, Sunish K. (Frontiers in Plant Science, 2018)
Spot blotch (SB) caused by Cochliobolus sativus (anamorph: Bipolaris sorokiniana) is an economically important disease of wheat worldwide. Under a severe epidemic condition, the disease can cause yield losses up to 70%. Previous approaches like bi-parental mapping for identifying SB resistant genes/QTLs exploited a limited to a portion of the available genetic diversity with a lower capacity to detect polygenic traits, and lower marker density. In this study, we performed genome-wide association study (GWAS) for SB resistance in hard winter wheat association mapping panel (HWWAMP) of 294 genotypes. The HWWAMP was evaluated for response to Bipolaris sorokiniana (isolate SD40), and a range of reactions was observed with 10 resistant, 38 moderately resistant, 120 moderately resistant- moderately susceptible, and 111 moderately susceptible and 15 susceptible genotypes. GWAS using 15,590 high-quality SNPs and 294 genotypes we identified six QTLs (p= <0.001) on chromosomes 2D, 3A, 4A, 4B, 5A, 7B that collectively explained 30% of the total variation for SB resistance. Highly associated SNPs were identified for all six QTLs, QSb.sdsu-2D.1 (SNP: Kukri_c31121_1460, R2 = 4%), QSb.sdsu-3A.1 (SNP: IAAV2383, R2 = 4 %), QSb.sdsu-4A.1 (SNP: IWA8475, R2 = 5.5%), QSb.sdsu-4B.1 (SNP: Excalibur_rep_c79414_306, R2 = 4 %), QSb.sdsu-5A.1 (SNP: Kukri_rep_c104877_2166, R2 = 6%), and QSb.sdsu-7B.1 (SNP: TA005844-0160, R2 = 6%). Our study not only validates three (2D, 5A, 7B) genomic regions identified in previous studies but also provides highly associated SNP markers for marker assisted selection. In addition, we identified three novel QTLs (QSb.sdsu-3A.1, QSb.sdsu-4A.1, QSb.sdsu-4B.1) for SB resistance in wheat. Gene annotation analysis of the candidate regions identified nine NBS-LRR and 38 other plant defense-related protein families across multiple QTLs, and these could be used for fine mapping and further characterization of SB resistance in wheat. Comparative analysis with barley indicated the SB resistance locus on wheat chromosomes 2D, 3A, 5A, and 7B in our study are syntenic to the previously identified SB resistance locus on chromosomes 2H, 3H, 5H, and 7H in barley. The ten highly resistant genotypes and SNP markers identified in our study could be very useful resources for breeding of SB resistance in wheat.